Pregnancy and associated factors among teenage females in Hula District, Sidama region, Ethiopia: a community-based cross-sectional study - Amenu, Mekdes; Tediso, Dansamo; Feleke, Tihun; Fantahun, Selam; Woldesemayat, Endrias Markos (Frontiers in Reproductive Health, 2024)
BackgroundTeenage pregnancy causes serious health, social, and economic consequences, with 95% occurring in developing countries. A significant number of girls start childbearing at an early age in Ethiopia, which contributes to high infant and maternal morbidity and mortality. However, the information on teenage pregnancy and related variables is limited in the study area.ObjectiveTo assess the prevalence of teenage pregnancy and its associated factors among teenage females in the Hula District, Sidama, Ethiopia.MethodsA community-based cross-sectional study was employed among 518 teenagers, randomly selected between 15 February and 15 March 2023. An interviewer-administered questionnaire was used for data collection. Bivariate and multivariate logistic regression analyses were applied to assess the relationship under study.ResultsLiving in rural areas compared to urban [adjusted odds ratio (AOR) = 3.90; 95% confidence interval (CI): 1.30–11.3], lack of awareness about family planning methods (AOR = 5.90; 95% CI: 1.60–22.24), unfamiliarity with the availability of family planning services (AOR = 3.20; 95% CI: 1.08–9.24), and inadequate communication about sexual issues with parents (AOR = 3.61; 95% CI: 1.14–11.56) were independently associated with teenage pregnancy.ConclusionThe prevalence of teenage pregnancies in the Hula District was high. Factors such as residing in rural areas, limited access to information on family planning methods and services, as well as a lack of open discussions about sexual health were associated with teenage pregnancy.